Compression rates of untreated and stabilized peat soils - Sing, W.L.; Hashim, Roslan; Ali, F.H. (2008)
Characterized by high initial void ratio, organic content and water holding capacity, fibrous peat exhibits high compressibility and low shear strength. Consequently, formation of deep fibrous peat layer often poses difficulties in construction. In practice, compressibility of deep fibrous peat layer can be reduced by deep soil stabilization technique. The technique is developed in such a way that dry binders are mixed with in situ peat soil to form columnar reinforcement in the deep peat ground prior to preloading. Preloading simulations of both untreated and stabilized peats were carried out in laboratory by loading of both soils using standard oedometer consolidation apparatus. Ordinary Portland cement, ground granulated blast furnace slag and siliceous sand were used to stabilize the soil. Analysis on the time-compression curves from the tests revealed that coefficients of vertical consolidation (cv of both soils were best predicted using square root of t52.6 method when compared to those evaluated using conventional curve fitting methods. Main reason for this is the experimental time-compression curves for the method best fit its theoretical curve. In addition, the method predicts cv of soil at 52.6 average degree of consolidation, which is less likely to be affected by secondary compression that usually occurs concurrently at the later stage of soil primary consolidation.